Shoulder, arm, and elbow injuries in soccer players - Almeida, Gonçalo G.; Afonso, P. Diana (Skeletal radiology, 2025)
Soccer is a global widespread sport with a high injury rate, mostly to the lower limbs. Even though upper limb injuries are much less common among soccer players, their prevalence has increased in recent years. This is due to several reasons/factors, including new and more aggressive tactics, a rise in the number of younger players with different levels of skeletal maturation, and due to the growth of women’s participation in sports, which is in line with the fast progression in the degree of professionalism in women’s soccer. This review paper aims to (a) describe the most common injuries in the shoulder, arm, and elbow in soccer players and (b) to show the role of different imaging modalities in diagnosing upper extremity injuries that can occur in this sport. Familiarity with these injuries and their mechanisms will lead to a quicker diagnosis and correct reporting of imaging of soccer players.